(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Over the past years, many people around the world have been studying foreign languages, in particular English. Knowledge of foreign languages opens up unlimited opportunities for people in almost all spheres of Education, Economics, Culture, Tourism and the other related subjects. In this article, the author discusses in detail the importance of the methodology for learning foreign languages and learning English, as well as the ability to use modern technologies in the process of Language Teaching.